2004
DOI: 10.1038/sj.onc.1207610
|View full text |Cite
|
Sign up to set email alerts
|

The carcinoma-associated antigen EpCAM upregulates c-myc and induces cell proliferation

Abstract: Epithelial cell adhesion molecule (EpCAM) is a membrane glycoprotein expressed on adenomatous and simple epithelia, where it is involved in homophilic adhesion at the basolateral membrane. Carcinomas strongly overexpress EpCAM through an, as yet, unknown mechanism. Interestingly, otherwise EpCAM-negative squamous epithelia are seen to express EpCAM concomitant with their transformation and de-differentiation. The amount of EpCAM and the number of expressing cells both increase with the grade of dysplasia. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
287
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(306 citation statements)
references
References 28 publications
9
287
1
9
Order By: Relevance
“…In 2004, first evidence for a direct role of EpCAM in growth-promoting nuclear signalling was reported (Munz et al, 2004). These data and results published by the group of Gillanders (Osta et al, 2004) revived research on the biological function of EpCAM, which is now delivering breakthrough results.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In 2004, first evidence for a direct role of EpCAM in growth-promoting nuclear signalling was reported (Munz et al, 2004). These data and results published by the group of Gillanders (Osta et al, 2004) revived research on the biological function of EpCAM, which is now delivering breakthrough results.…”
mentioning
confidence: 98%
“…This name is proposed to be EpCAM (without a dash) as an abbreviation for the ability of the protein to act as an epithelial-specific cell adhesion molecule (Litvinov et al, 1994) and activating molecule (Munz et al, 2004;Osta et al, 2004). It is also suggested to add in brackets on the first occurrence of the EpCAM name in a text the recently introduced cellular differentiation (CD) marker nomenclature for EpCAM, namely CD326.…”
mentioning
confidence: 99%
“…Munz et al (2004) reported that Ep-CAM upregulated c-myc and induced cell proliferation, and Osta et al (2004) reported that specific ablation of Ep-CAM expression using RNA interference resulted in a dramatic decrease in the invasive potential of breast cancer cell lines. Furthermore, Sankpal et al (2009) reported that transcriptional repression of Ep-CAM expression activated breast cancer invasion controlled by p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, EpCAM is expressed on socalled cancer stem cells in breast cancer and only those stem cells expressing EpCAM are highly tumorigenic in immunodeficient mice [52]. Fourthly, knockdown of Ep-CAM expression by a specific small inhibitory RNA in breast cancer cell lines inhibited proliferation, migration and invasiveness of cancer cells [53], and overexpression of EpCAM in quiescent cells increased these oncogenic parameters [54]. Based on the present data and the emerging biology of EpCAM in breast cancer, MT110 appears as an attractive therapeutic option for treatment of metastatic and therapeutic resistant stages of the disease.…”
Section: Discussionmentioning
confidence: 99%